Induction of ferroptosis using functionalized iron-based nanoparticles for anti-cancer therapy. (15th December 2022) - Bae, Chaewon; Kim, Hyerim; Kook, Yun-Min; Lee, Chaedong; Kim, Changheon; Yang, Chungmo; Park, Min Hee; Piao, Yuanzhe; Koh, Won-Gun; Lee, Kangwon
Abstract: Ferroptosis, a cell death pathway that is induced in response to iron, has recently attracted remarkable attention given its emerging therapeutic potential in cancer cells. The need for a promising modality to improve chemotherapy's efficacy through this pathway has been urgent in recent years, and this non-apoptotic cell death pathway accumulates reactive oxygen species (ROS) and is subsequently involved in lipid peroxidation. Here, we report cancer-targeting nanoparticles that possess highly efficient cancer-targeting ability and minimal systemic toxicity, thereby leading to ferroptosis. To overcome the limit of actual clinical application, which is the ultimate goal due to safety issues, we designed safe nanoparticles that can be applied clinically. Nanoparticles containing ferroptosis-dependent iron and FDA-approved hyaluronic acid (FHA NPs) are fabricated by controlling physicochemical properties, and the FHA NPs specifically induce ROS production and lipid peroxidation in cancer cells without affecting normal cells. The excellent in vivo anti-tumor therapeutic effect of FHA NPs was confirmed in the A549 tumor-bearing mice model, indicating that the induction of FHA NP-mediated cell death via the ferroptosis pathway could serve as a powerful platform in anticancer therapy. We believe that this newly proposed FHA NP-induced ferroptosis strategy is a promising system that offers the potential for efficient cancer treatment and provides insight into the safe design of nanomedicines for clinical applications. Graphical abstract: Image 1